Projected Impact of Urbanization on Cardiovascular Disease in China - Chan, Faye (2012)
OBJECTIVES: The Coronary Heart Disease (CHD) Policy Model-China, a national scale cardiovascular disease computer simulation model, was used to project future impact of urbanization. METHODS: Populations and cardiovascular disease incidence rates were stratified into four submodels: North-Urban, South-Urban, North-Rural, and South-Rural. 2010 was the base year, and high and low urbanization rate scenarios were used to project 2030 populations. RESULTS: Rural-to-urban migration, population growth, and aging were projected to more than double cardiovascular disease events in urban areas and increase by 27.0–45.6% in rural areas. Urbanization is estimated to raise age-standardized coronary heart disease incidence by 73–81 per 100,000 and stroke incidence only slightly. CONCLUSIONS: Rural-to-urban migration will likely be a major demographic driver of the cardiovascular disease epidemic in China.